Features and functional importance of key residues of the Mycobacterium tuberculosis cytochrome bd oxidase - Sviriaeva, Ekaterina (2021)
Cytochrome bd (cyt-bd) oxygen reductases have a high affinity to oxygen and use the two electrons provided by ubiquinol or menaquinol, like in mycobacteria, to reduce oxygen to water. Although they do not pump protons from the cytoplasmic to the periplasmic side, they generate a proton motive force due to the release of protons after quinol oxidation. Here, we show that the mycobacterial cyt-bd has a number of specific features, including a 17-residue stretch (307SGVTLQGIRDLQQEYQQ323) near the Q-loop of the Mycobacterium tuberculosis subunit CydA and a 412QLVRLTVKA420 region on the periplasmic side. Site directed mutagenesis and whole-bacteria assays demonstrated that these mycobacteria-specific stretches are essential for the oxidase’s function. Single amino acid substitutions around the 307SGVTLQGIRDLQQEYQQ323 stretch revealed the importance of the aromatic residue Y330 in oxygen consumption and consequently in ATP synthesis. A moderate reduction and no effect was observed for mutants F325 and Y321, respectively, while the double mutant CydAY321/F325 drastically reduced enzyme activity. In addition, single mutants of the mycobacterial cyt-bd were generated to probe the role of proposed critical residues for proton shuffling. Further data demonstrate that amino acids W64 and F18 in the CydB subunit might be important as any slight destabilization of the hydrophobic environment near them makes the enzyme inactive. Finally, the potential of the mycobacterial cyt-bd as a drug target is discussed.